Indigenous Knowledge and Intellectual Property Rights - Prakash, Siddhartha (World Bank, Washington, DC, 2012)
The note emphasizes the critical importance of documenting indigenous knowledge in writing, which can then be used to challenge a patent claim on knowledge that is already in the public domain. It also highlights the usefulness of other forms of intellectual property rights, other than patents, such as geographical indicators. These may be of more use to indigenous communities seeking to regulate access over their resources, as they can be applied to knowledge that evolves over time, and with the input of the local community at large. This leads us to the possibility of widening the Agreement on Trade-Related Intellectual Property Rights (TRIPS), to ensure that patents disclose the origin of genetic resources, and use of indigenous knowledge, and, consider sui generis forms of intellectual property, such as community based rights, to secure equitable benefit sharing.